Music Sketches - Sallis, Friedemann (Cambridge Cambridge University Press, 2015)
The term 'music sketch' relates to the vast variety of documents that are used by composers to work out a musical technique or idea and to prepare their work for performance or publication. These documents can often provide crucial insights into authorship, biography, editorial practice and musical analysis. This introduction provides students and scholars with the knowledge and skills they need to embark on research projects involving the study of composers' working documents. Presenting examples of the compositional process over a 400-year period, it includes a selection of detailed case studies on how sketches were created and the techniques that were used, such as transcription and the sorting of loose leaves. Numerous illustrations of manuscripts and autographs, many of which have never been published before, show how these vital documents can be used to better understand compositional processes.